A frequency domain formulation of the singular boundary method for dynamic analysis of thin elastic plate. (January 2019) - Sun, Linlin; Wei, Xing
Abstract: This paper presents a frequency domain formulation of the singular boundary method (SBM) for the analysis of thin elastic plates subjected to dynamic loads. In the SBM, the fundamental solutions for the dynamic thin plate problem in frequency domain are taken as basis functions. To isolate the singularities, we derive the origin intensity factors (OIFs) for the kernels of the SBM which allows the source points to coincide with the collocation points. For the transient analysis, the exponential window method (EWM) is applied in conjunction with the SBM to obtain the time-domain result. To demonstrate the efficiency and accuracy of the present method, several examples under harmonic and transient loads are carried out in comparison with the exact solutions and finite element solutions.